A map of days - Riggs, Ransom (Quirk Books, 2018)
Having defeated the monstrous threat that nearly destroyed the peculiar world, Jacob Portman is back where his story began, in Florida. Except now Miss Peregrine, Emma, and their peculiar friends are with him, and doing their best to blend in. But carefree days of beach visits and normalling lessons are soon interrupted by a discovery-a subterranean bunker that belonged to Jacob's grandfather, Abe. Clues to Abe's double-life as a peculiar operative start to emerge, secrets long hidden in plain sight. And Jacob begins to learn about the dangerous legacy he has inherited-truths that were part of him long before he walked into Miss Peregrine's time loop. Now, the stakes are higher than ever as Jacob and his friends are thrust into the untamed landscape of American peculiardom-a world with few ymbrynes, or rules-that none of them understand. New wonders, and dangers, await in this brilliant next chapter for Miss Peregrine's peculiar children. Their story is again illustrated by haunting vintage photographs, now with the striking addition of full-color images interspersed throughout for this all-new, multi-era American adventure.